Genome engineering of Stx1-and Stx2-converting bacteriophages unveils the virulence of the dairy isolate Escherichia coli O174:H2 strain UC4224 - Milani, Giovanni; Belloso Daza, Mireya Viviana; Cortimiglia, Claudia; Bassi, Daniela; Cocconcelli, Pier Sandro (Frontiers in Microbiology, 2023)
The past decade witnessed the emergence in Shiga toxin-producing Escherichia coli (STEC) infections linked to the consumption of unpasteurized milk and raw milk cheese. The virulence of STEC is primarily attributed to the presence of Shiga toxin genes (stx1 and stx2) carried by Stx-converting bacteriophages, along with the intimin gene eae. Most of the available information pertains to the “Top 7” serotypes associated with STEC infections. The objectives of this study were to characterize and investigate the pathogenicity potential of E. coli UC4224, a STEC O174:H2 strain isolated from semi-hard raw milk cheese and to develop surrogate strains with reduced virulence for use in food-related studies. Complete genome sequence analysis of E. coli UC4224 unveiled the presence of a Stx1a bacteriophage, a Stx2a bacteriophage, the Locus of Adhesion and Autoaggregation (LAA) pathogenicity island, plasmid-encoded virulence genes, and other colonization facilitators. In the Galleria mellonella animal model, E. coli UC4224 demonstrated high pathogenicity potential with an LD50 of 6 CFU/10 μL. Upon engineering E. coli UC4224 to generate single and double mutant derivatives by inactivating stx1a and/or stx2a genes, the LD50 increased by approximately 1 Log-dose in the single mutants and 2 Log-doses in the double mutants. However, infectivity was not completely abolished, suggesting the involvement of other virulence factors contributing to the pathogenicity of STEC O174:H2. Considering the possibility of raw milk cheese serving as a reservoir for STEC, cheesemaking model was developed to evaluate the survival of UC4224 and the adequacy of the respective mutants as reduced-virulence surrogates. All tested strains exhibited the ability to survive the curd cooking step at 48°C and multiplied (3.4 Log CFU) in cheese within the subsequent 24 h. These findings indicate that genomic engineering did not exert any unintended effect on the double stx1-stx2 mutant behaviour, making it as a suitable less-virulent surrogate for conducting studies during food processing.